2009
DOI: 10.1111/j.1365-2621.2009.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion process on antioxidant activity, total phenolics and β‐glucan content of extrudates developed from barley‐fruit and vegetable by‐products

Abstract: The aim of this study was to determine the effects of extrusion processing variables on antioxidant activity (AA), total phenolic content (TP) and b-glucan content (BG) of extrudates. Products were prepared by extrusion cooking of barley flour, barley flour-tomato pomace and barley flour-grape pomace blends. Antioxidant activity as measured by the DPPH method was 43.17 ± 0.362, 27.57 ± 0.120 and 82.23 ± 0.785% while TPs, expressed as ferulic acid equivalents, were 5.29 ± 0.126, 4.66 ± 0.023 and 9.15 ± 0.015 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 28 publications
5
78
0
3
Order By: Relevance
“…Shih et al (2009) investigated the effects of extrusion on the TAC of sweet potato and reported that the scavenging effect on DPPH radicals increased. However, Altan et al (2009) found that the extrusion decreased TAC and TPC of barley, barley-tomato pomace, whereas others reported no effect (Ş ensoy et al 2006;Altan et al 2009). …”
Section: Effect Of Processing Methods On the Antioxidant Capacitymentioning
confidence: 89%
“…Shih et al (2009) investigated the effects of extrusion on the TAC of sweet potato and reported that the scavenging effect on DPPH radicals increased. However, Altan et al (2009) found that the extrusion decreased TAC and TPC of barley, barley-tomato pomace, whereas others reported no effect (Ş ensoy et al 2006;Altan et al 2009). …”
Section: Effect Of Processing Methods On the Antioxidant Capacitymentioning
confidence: 89%
“…22 Nevertheless, the relative superiority of extrusion is not obvious as many authors have still found a great loss (more than 50%) of phenolics during extrusion. 20,23,24 This dilemma was somewhat reversed when the thermostable a-amylase was introduced into cereal extrusion (mainly to achieve a high degree of starch gelatinization and liquefaction in the industries of starch saccharication, cake making, ethanol fermentation and liquor brewing) because the phenolics seem to be indirectly protected both in free and bound forms. 3,19,25,26 The mechanism of rapid starch gelatinization coupled with total phenolic retention during bioextrusion is still ambiguous, in spite of the otherwise complex impact of extrusion processing (without an enzyme catalyst) on the chemical and antioxidative prole, considering the multiple operating factors of temperature, moisture content, shear force, local friction and mechanical energy.…”
Section: -14mentioning
confidence: 99%
“…The enzymatic hydrolysis of rice starch was well conducted as lower DP (<0.1 Mpa) and SME (94.5-181 kJ kg À1 ) were tested for enzymatic extrusion (Table 1). Furthermore, the k G values of both TE and EE had a positive relation to N ( 20 and other mixtures of cereal ours. 42 We also found that enzyme addition did not change but deepened the negative connection between c/c 0 and N (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that additives used as powders, extracts, concentrates, or byproducts from different sources can substantially change the food's physical characteristics and thus potentially affect its acceptability. Such characteristics include water absorption index, bulk density, water solubility index, expansion index, texture, and color [14][15][16][17]. The aim of the present study was to evaluate the changes in these physicochemical properties following the addition of 2.5, 5.0, and 7.5% (w/w) red cactus pear encapsulated powder to pigment extruded cereal.…”
Section: Introductionmentioning
confidence: 99%